1999
DOI: 10.1002/(sici)1521-3935(19990101)200:1<95::aid-macp95>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Cesium fluoride-mediated synthesis of aromatic polysulfides from aromatic dithiols and activated aromatic dihalides

Abstract: SUMMARY: The solution polycondensation of aromatic dithiols with activated aromatic dihalides like bis(4-fluorophenyl) sulfone with use of cesium fluoride as a base in polar aprotic solvents readily affords aromatic polysulfides having inherent viscosities as high as 1.0 dL/g. The polycondensation proceeds under essentially neutral and milder reaction conditions compared with the conventional method using potassium carbonate and with the cesium fluoride-assisted synthesis of aromatic polyethers as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The polycondensation was conducted under mild reaction conditions in DMAc using CsF or KF as a base to convert the hydroxyl group to the alkoxide anion for activating the reaction with DPSO. As illustrated in Scheme 2, in the reaction, CsF or KF also combines with HF, which is produced from the reaction as a byproduct, to form a CsHF 2 or KHF 2 complex that precipitates out of the solution, [7][8][9] allowing the reaction to go to completion, generating a high molecular weight polymer.…”
Section: Resultsmentioning
confidence: 99%
“…The polycondensation was conducted under mild reaction conditions in DMAc using CsF or KF as a base to convert the hydroxyl group to the alkoxide anion for activating the reaction with DPSO. As illustrated in Scheme 2, in the reaction, CsF or KF also combines with HF, which is produced from the reaction as a byproduct, to form a CsHF 2 or KHF 2 complex that precipitates out of the solution, [7][8][9] allowing the reaction to go to completion, generating a high molecular weight polymer.…”
Section: Resultsmentioning
confidence: 99%
“…This reaction represents a completely different mechanism to that associated with the chain degradation of non-fluorinated polyether ketones and sulfones, [14][15][16][17][18][19][20] where the center of the degradation is the ether group. Clearly in the case of the fluorinated polymers, the ketone groups are more sensitive to nucleophilic attack than ether groups.…”
Section: Highly Fluorinated Poly(arylene Ether Ketone) Prepared By a mentioning
confidence: 99%
“…The presence of trace amounts of water in association with fluoride ions produced during the reaction in the solution will cause serious polymer degradations by side reactions such as hydrolysis and chain scission. [17][18][19][20] It has been reported that the introduction of calcium or magnesium carbonates into the reaction associated with an alkali metal carbonate facilitates the polycondensation. [21][22][23][24][25] Very high molecular weight poly(arylene ether)s have been synthesized when a mixture of calcium carbonate and a small amount of potassium carbonate is used, whereas only low molecular weight polymers are produced using potassium carbonate alone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dichloroketones can be good monomers if the nucleophilicity of the coreactant is higher than that of the phenol. It has been reported that high molecular weight poly(thioetherketone)s (PTEKs) 10,11 or poly(thioether-sulfone)s 12,13 have been obtained when highly nucleophilic thiophenol derivatives were used as monomers with a dichloroketone or dichlorosulfone, respectively. However, PTEKs have been paid much less attention.…”
Section: Introductionmentioning
confidence: 99%